Challenge of politics: an introduction to politics science - Riemer, Neal; Simon, Douglas W.; Romence, Joseph (New delhi, 2016)
This book enables students to see how the subfields of political science converge around a set of crucial questions: can we as citizens and students articulate and defend a view of the good political life and its guiding political values? Can we bring political wisdom to bear on judgments about politics and public issues? Can we develop a science of politics to help us understand significant political phenomena$1 (Bthe empirical realities of politics? s
Keywords: Politics science